PROYECTO DE FACTIBILIDAD PARA CREAR UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE CEBOLLA BLANCA DE RAMA EN POLVO (Allium Fistulosum), EN LA CIUDAD DE LOJA - Pérez Orellana, María José (2015)
This project aims to fill a need feasibility of housewives by offering an innovative and natural product as an alternative for families in our town have an seasoning in food preparation giving good flavor to your food, using terms as natural raw white onion branch. To develop the research work called the overall objective was determined: "FEASIBILITY STUDY FOR CREATING A producer and marketer RAMA WHITE ONION POWDER (Allium fistulosum) IN THE CITY OF LOJA" and specific objectives: 1. Conduct a market study to determine the supply and demand existing onion powder in the city of Loja; 2. Develop technical study to define the size, location and project engineering; 3. Perform organizational design with the appropriate legal basis; 4. Conduct a study to determine the financial investment, financing sources and resources needed and 5. Determine the financial evaluation through financial indicators; All this was accomplished with the application of deductive, inductive and quantitative methods; techniques such as direct observation, interview and survey of the families of the city of Loja who are potential consumers allowing the product to meet demand. Market research yielded data of potential demand, real and effective and meet the market vendor "ILE" Industry Lojana of Spiceries who currently produces and sells red onion powder, information used to establish the unmet. On the 5 technical study determined that the company work with an installed capacity (438,000 pounds), operating with a 24.11% capacity utilization offering to market in the first year 105,600 pounds a year, will be located in the city of Loja, neighborhood Capulí having adequate distribution thereof; as well as materials, equipment, and machinery required for the production of white onion powder branch inputs. Legal and organizational aspects which are a fundamental part in the operation of the company were identified. The study found the overall financial investment to launch the project, which amounted to $ 77,951.40 with 26% of external financing and the remaining partners' capital 74%; once made projections of revenues and expenditures, project feasibility throwing a net present value (NPV) positive was determined; an internal rate of return (IRR) greater than the opportunity cost, the capital recovery period will be within the lifetime of the project; the benefit cost 69 cents for every dollar invested in the project and its sensitivity analysis indicates that the project supports changes in both its revenue and expenditure. Results allowed to conclude that the project is feasible, so that execution is recommended to give a return to its investors and generates productive development in the city of Loja.